Distribution, Development, Stabilizer, and Consumers Areas of Livestock and Forages-Based Crops; An Emperical Status of Bordered Keerom Regency, West New Guinea-Indonesia - Mulyadi, Mulyadi; Gusbager, Piter; Sagrim, Meky; Runtuboi, Yubelince Yustencin; Iyai, Deny Anjelus; Inriani, Noveling; Baaka, Alnita; Pakage, Stepanus (Faculty of Animal Science, Universitas Brawijaya, 2024)
Distribution, development, stabilizer, and consumer areas status of livestock development become the objective of this research. Little is known concerning the portrait of livestock production in the neighborhood region of Indonesia and Papua New Guinea such as Keerom Regency in Papua Province. The descriptive method employed was using desk study. The measured parameters were population structure, carrying capacity, regional development, and suitability commodity using LQ. The finding shows that Skanto and Arso Timur hold the first two districts with a high population of the goat. The 2 districts out of 11 districts have no swine recorded. The Skanto District has the highest cattle population recorded, i.e. 4136,38 AU, followed by Arso Timur, Arso, and Arso Barat. Production of fodder from crop yields is harvested from Senggi and Arso, followed by Skanto, Web, Arso Barat, Yaffi, and Arso Timur. Corn is the highest production of crops. Senggi can be a central of livestock development, followed by Arso, Skanto, Web, and Arso Barat. The KPPTR calculation for Keerom regency shows Web district has the highest value of 379.31 ST, while the lowest is Skanto. The goat sector from the point of agribusiness density shows optimum values reached by the Skanto district. The cattle sector from the point of regional density is dominantly shown by Arso Barat. The cattle sector from the point of economic density is dominantly shown by the Skanto district. The criterion found commonly is very dense compared to dense, medium, and rare. The total values of this finding range from 6 to 12 for EU, EW, and UW. In the EU, the WK (CA) of the three commodities is greater found, i.e. 18 areas compared to WPP (DDA) only found 13 areas. The figures for cattle are under 0,50, not achieving 1,00 and greater than that of 1,00. Only in the Skanto district, the LQ mark of the goat reached 0,539. However, swine is the common livestock raised by farmers in Keerom Regency.